The impact of cultural differences and moral intensity on ethical decision-making: Evidence from France and China - Husser, Jocelyn; Goujon Belghit, Anne; Song, Lingfang; Rouanet, Anaïs (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
The originality of this study lies in its investigation of cultural differences in the ethical decision-making process of purchasers. Our research mobilizes six scenarios that reproduce typical purchasing situations in France and China. A sample of 366 professional purchasers (203 French and 163 Chinese) was used to examine the six characteristics of the decision-making process developed by Jones (1991).Our research indicates that Chinese purchasers recognize ethical issues more than French purchasers and intend to act in a more ethical way regarding one dimension defined: proximity. By contrast, French purchasers intend to act in a more ethical way than Chinese buyers regarding three other dimensions: temporal immediacy, probability of effect and concentration of effect.